A 3-year prospective randomized clinical trial of alveolar bone crest response and clinical parameters through 1, 2, and 3 years of clinical function of implants placed 4 months after alveolar ridge preservation using two different allogeneic bone-grafting materials - Önder Solakoğlu; Duygu Ofluoğlu; Heidi Schwarzenbach; Guido Heydecke; Daniel Reißmann; Sertan Ergun; Werner Götz (SpringerOpen, 2022)
Abstract Purpose The aim of this study was to longitudinally evaluate changes in alveolar bone crest (ABC) levels and differences in resorption rates (RR) between the tested grafting materials following alveolar ridge preservation (ARP) after tooth extraction after 1, 2, and 3 years (T1-T8) of clinical function. Methods Patients were randomly assigned to two different bone allografts (group 1 maxgraft®, group 2 Puros®) for ARP. Non-restorable teeth were minimal traumatically extracted. Sockets were augmented with the tested materials and covered with a pericardium membrane. After 4 months of healing, 36 implants were placed and sites were clinically and radiographically monitored in the mesial (ABC-M), the distal (ABC-D, T1-T8), the bucco-lingual (ABC-BL), buccal (ABC-B) and oral (ABC-O) aspect (T1-T4). Results Changes in (ABC-M), (ABC-D), (ABC-BL), (ABC-B), and (ABC-O) levels showed statistically highly significant differences between T1 and T2 for both bone allografts (p < 0.001). Changes at the ABC-M and ABC-BL levels between T2 and T3 of group 1 showed a statistically significant difference (p < 0.001). Both groups achieved and maintained increased ABC levels without statistically significant differences throughout the monitoring periods of 1-3 years (T6-T8) of clinical function. No failures or adverse events were observed. Conclusions To the best of our knowledge, this study is within its limitations the first study to directly compare ABC-changes and differences in RR of two different allogeneic grafting materials for a period of 3 years after ARP. It was demonstrated to be, despite significant differences in RR, a successful method of preserving increased ABC levels through 1, 2, and 3 years of clinical function. Trial registration DRKS00013010, registered 07/30/2018, http://apps.who.int/trialsearch